Pengembangan Aplikasi Pendaftaran Forum Diskusi Berbasis Web Menggunakan Kombinasi Algoritma Decision Tree Dan Random Forest - Yuniati, Yuyun; Andrianingsih, Andrianingsih; Fitri, Iskandar (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
A discussion forum is a place that aims to carry out activities by discussing something or exchanging ideas with the aim of knowing common interests. This study aims to simplify the process of a registration system for discussion forum participants so that participant data is more structured by classifying participant data into 2 types, namely ordinary participants and competitor participants. Ordinary participants are participants who participate in all series of activities without being competitors in discussion forum activities, while competitor participants are participants who participate in all series of activities and can make presentations. The research method used is a combination of Decision Tree and Random Forest algorithms, namely a structured or sequential method from the concept planning, modeling, implementation, testing and maintenance stages. In this case, it is necessary to create a website with a management information system design. The information system in making this website must systematically be structural and the technology used for website creation, namely: PHP, HTML, CSS, with a database system using MySQL. The designs that have been designed are starting from the login menu, participant data, participant assignments, materials, participant scores up to the logout menu, while testing has been carried out by accessing the website by 20 users at the same time and can be generated by calculating the seconds obtained From these tests, the database used is increasing, namely 600, 800 to 1,000 participant databases.